Uterine leiomyomas and anaemia in women - Malinowski, Andrzej; Maciołek-Blewniewska, Grażyna; Hęsiak, Marek; Mikołajczyk, Rafał (Menopause Review/Przegląd Menopauzalny, 2004)
The most common tumours of female genital organs are uterine myomas, its occurred in one to three gynaecological patients and from 10 to 20 percent of women population. Observed anaemia in medical practice is often presented in women with uterine myomas. A differentiation of iron deficiency without anaemia and anaemia with iron deficiency is still essential. This work presents reasons of anaemia in women with uterine myomas and influence of hysterectomy on ferritin’s concentration in serum of blood and others haematological parameters.